Cholecystitis with fistula stomach and intestine: A case report (International Seven Journal of Health Research, 2024)
Introduction: Cholecystitis is an inflammatory condition of the gallbladder that can range from a controlled condition to a potentially fatal condition. Gastrointestinal fistulas are severe surgical complications that can occur in various clinical forms and are responsible for increasing the morbidity and mortality of surgical procedures. The complication of cholecystitis due to fistula in the gastrointestinal tract presents variable and nonspecific clinical manifestations, and its diagnosis is often made incidentally in the perioperative period of its underlying cause, and treatment is based on the removal of the gallbladder and correction of the fistula. Objective: To demonstrate the importance of an early diagnosis of cholecystitis, thus preventing possible complications, such as a fistula. Methods: From a medical case that occurred at the Santa Casa da Misericórdia de Presidente Prudente, and its medical records, information was collected to carry out this report. Results: Considering that the diagnosis of gallbladder cancer is made in the postoperative period and its treatment is precisely surgical, laparoscopic cholecystectomy is chosen as a therapeutic modality, even though the definitive indications for this method are still controversial. Conclusion: Cholecystitis aggravated by tumor has a difficult prognosis due to factors such as aggressive tumor biology, anatomical position of the gallbladder, and late diagnosis, which when associated with personal risk history can lead to complications such as the formation of gastrointestinal fistulas. Therefore, an early diagnosis, using histological or imaging tests and appropriate surgical treatment, as well as postoperative follow-up is crucial to ensure a recovery without complications.